Programmable Universal Filter and Quadrature Oscillator Using Single Output Operational Transconductance Amplifiers - Knobnob, Boonying; Torteanchai, Usa; Kumngern, Montree (My University, 2021)
This paper presents a new programmable universal filter and quadrature oscillator based on the single output operational transconductance amplifiers (OTAs). The proposed universal filter and quadrature oscillator can be achieved into single topology by programming analog switches. When the circuit performs as a universal filter, it can realize low-pass, high-pass, band-pass, band-stop and all-pass filters with orthogonal and electronic controls of the natural frequency and quality factor. When the circuit performs as a quadrature oscillator, it provides a three-phase quadrature output signal which the condition and frequency of oscillations can be controlled orthogonally and electronically. The proposed structure can be realized based on the single output OTAs which are easily implemented as both commercially available integrated circuits (ICs) as OTAs and complementary metal-oxide semiconductor (CMOS) OTAs as IC forms. SPICE simulation using standard 0.18 µm CMOS process is used for investigating the performance of the proposed circuit whereas the workability of new circuit is confirmed by LM13600 discrete-component integrated circuits as OTAs.
Keywords: Analog signal processing; Operational transconductance amplifier; Quadrature oscillator; Universal filter; Voltage-mode circuit